Bronchodilatation and the site of airway resistance in severe chronic bronchitis. Issue 1 (February 1979) - Douglas, N J; Davidson, I; Sudlow, M F; Flenley, D C
Abstract : Twenty-one patients with severe chronic bronchitis and emphysema (FEV1 less than 1 1) inhaled 80 microgram of the atropine-like agent ipratropium or placebo in a double-blind study and three hours later inhaled 200 microgram salbutamol. After 80 microgram ipratropium, mean FEV1 was significantly greater than after 200 microgram salbutamol (P less than 0.025), but the difference was only 40 ml and the clinical significance of this difference is unproved. There was no correlation between the patient's response to ipratropium and the response to salbutamol. When salbutamol was administered three hours after ipratropium, the FEV1 rose to higher levels than after either agent alone (P less than 0.01). Studies breathing 80% helium/20% oxygen suggest that ipratropium dilates both large and small airways. There was no correlation between the response to helium/oxygen and the response to either bronchodilator. The results suggest that in severe chronic bronchitis and emphysema ipratropium is at least as effective as salbutamol, and that such patients should have reversibility studies with salbutamol alone, ipratropium alone, and after both agents together. The combination of ipratropium and salbutamol may be clinically useful.